AB0109 Regulatory mechanism and importance of thrombospondin-1 (tsp-1) expression in rheumatoid synovial tissues: analysis by immunohistochemistry, in vitro fibroblast-like synovial cell culture and clinical evaluation. (23rd January 2014) - Suzuki, T.; Yamasaki, S.; Nakashima, Y.; Horai, Y.; Okada, A.; Kawashiri, S.-Y.; Iwamoto, N.; Ichinose, K.; Arima, K.; Tamai, M.; Nakamura, H.; Origuchi, T.; et al.
Abstract : Background: We have recently reported that serum immune complex containing thrombospondin-1 (TSP-1) is a novel biomarker in patients with rheumatoid arthritis (RA) (Ref. 1, 2 ), suggesting an abundant expression of TSP-1 in rheumatoid synovial tissues whereas the regulatory mechanism of TSP-1 expression remains to be unclear. Objectives: Present study is to investigate the regulatory mechanism of TSP-1 expression in fibroblast-like synovial cells (FLS) and patients with RA. Methods: Synovial tissues from patients with RA and osteoarthritis (OA) were obtained at the time of orthopedic surgery. Fibroblast-like synovial cells (FLS) were isolated from the rheumatoid synovial tissues and used for in vitro experiments. Expression of TSP-1 in the synovial tissues was examined by avidin-biotin complex method. Isolated rheumatoid FLS were cultured in the presence of varying cytokines including transforming growth factor b1 (TGF-b1), tumor necrosis factor a(TNF-a), interleukin-1 b(IL-1b), IL-6 or interferon g(IFN-g) for indicated hours. After incubation, expression of TSP-1 was investigated by quantitative reverse transcriptase polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA), respectively. For the clinical evaluation, plasma concentrations of TSP-1 and TGF-b1, serum concentration of vascular endothelial growth factor (VEGF), DAS28 and power Doppler (PD) score were prospectively examined in active RA patients who responded well to DMARDs treatment. All of patients gave their informed consent to be subjected to the protocol that was approved by the Institutional Review Board of Nagasaki University. Results: Expression of TSP-1 was prominent in the rheumatoid synovial tissues (N = 2) as compared with OA synovial tissues (N = 2), especially in the lining layer. Among cytokines examined, TGF-b1 was the most one to stimulate both mRNA expression (N = 4) (about 2 times) and protein expression (N = 4) (about 3.5 times) of TSP-1 from cultured rheumatoid FLS. High concentrations of TSP-1 (plasma), TGF-b1 (plasma) as well as VEGF (serum) with high DAS28 and PD score in patients with RA were noted before DMARDs treatments that were significantly inhibited after DMARDs treatments (N = 6, all patients were seropositive RA patients, respectively). Additionally, the decrement of TSP-1 was clearly correlated with that of TGF-b1. Conclusions: Abundant expression of TSP-1 from rheumatoid synovial tissues is supposed to be regulated by cytokines, especially TGF-b1. Since plasma concentration of TSP-1, clinical disease activity and ultrasound-determined vascularity were declined by DMARDs treatments, TSP-1 appears to be an important biomarker in RA and involve in angiogenesis of rheumatoid synovial tissues. References: Ohyama K, Ueki Y, Kawakami A, et al. Clin Chem 2011: 57; 905-9. Ohyama K, Kawakami A, Tamai M, et al. Ann Rheum Dis 2012: 71; 1916-7. Acknowledgements: n.p. Disclosure of Interest: None Declared